ANALISIS WISATA HALAL TERHADAP KEBERLANJUTAN WISATA RELIGIUS DI KABUPATEN OKU TIMUR - Yansahrita, Yansahrita; Renaldo, Riki; Iwari, M. Ichsan (STMIK Pringsewu, 2025)
This study aims to analyze the influence of halal tourism concepts on the sustainability of religious tourism in Ogan Komering Ulu (OKU) Timur Regency. Using a quantitative approach, data were collected through surveys involving tourists, tourism managers, and related stakeholders. The analysis focused on assessing how the implementation of halal tourism principles-such as the provision of facilities in accordance with Islamic guidelines-affects tourist satisfaction and the sustainable management of religious destinations in the region. The results show that the application of halal tourism standards has a positive impact on increasing tourist visits, strengthening the identity of religious destinations, and promoting sustainable tourism practices. This study recommends strengthening the implementation of halal tourism as a strategy to support the sustainable growth of religious tourism in OKU Timur Regency.